A web application to estimate the carbon footprint of constructed wetlands. (January 2021) - Andreo-Martínez, Pedro; Ortiz-Martínez, Víctor Manuel; Muñoz, Andrés; Menchón-Sánchez, Pablo; Quesada-Medina, Joaquín
Abstract: Constructed wetlands (CWs) are engineering systems recognized as an efficient and sustainable option to wastewater treatment. Due to the growing interest in CWs for waste management, the number of works analyzing their footprint and impact has risen in the last years. Thus, the study of these systems and their components in construction, operation, and demolition phases is important to characterize the technology and achieve a fully environmental-friendly approach. Until now, no complete tools for measuring both direct and indirect greenhouse gas (GHG) emissions in CWs have been reported in the field. Some efforts in this line are Life Cycle Assessment tools, which can be economically expensive and usually require specific training. Therefore, this work aims to present a web application as an open and complete tool for the estimation of GHG emissions in CWs, including both direct and indirect emissions and considering all the stages involved in their management. Highlights: A web-based application for calculating CO2 emissions in CW systems was developed. The tool is freely accessible through https://crftpr.herokuapp.com/ It provides emissions generated in construction, operation, and demolition stages. Validation tests and a running example have been also performed. The accuracy of the application has been demonstrated.